Development, Characterization and Stability of Bacaba Peel Extract Microemulsion Systems - Corrêa, Bruna Mendes; Piccoli, Ana Flávia Pereira; Barbosa, Flavia Rodrigues; Ribeiro, Elton Brito; Andrighetti, Carla Regina; Vasconcelos, Leonardo Gomes de; Battirola, Leandro Dênis; Valladao, Denia Mendes de Sousa (Fronteira: Journal of Social, Technological and Environmental Science, 2020)
Bacabeira (Oenocarpus bacaba MART.), a palm tree native from Amazon, has flavonoids found in its fruit peel with antioxidant activity, interesting to incorporate and stabilize in formulations in order to create drug vehicles with advantages. Thus, the aim of this work was to incorporate bacaba peel extract in microemulsions to assess its stability. All formulations contained pre-established quantities of distilled water, capric/caprylic triglycerides, Span 80Â® and Tween 80Â®, with 5 % of extract at 0.1 g mL-1 added. From the 72 tested formulations, eight produced microemulsions and were subjected to centrifugation, physicochemical characterization and stability studies, with four sustaining their physical stability. All samples showed Newtonian profile and linear viscosity. The droplets size did not exceed 325 nm of hydrodynamic diameter. Test for antioxidant activity showed satisfactory. Therefore, it was possible to develop microemulsions from peel bacaba with stability that is suitable for their use as drug vehicles.